The circles of life (2) Look back in anger? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
We live in a young world, but we must not forget our past.15 October 1999. A two-hour ceremony of some of the great and the good of the world is held at the headquarters of the Food and Agriculture Organization in Rome, Italy. The event marks World...